Penyuluhan Hukum Pencegahan Kekerasan dalam Rumah Tangga sebagai Upaya Penanggulangan Kejahatan - Mansyah, Muh Sutri; Nurcahyo, Edy; Zudin, Zudin; Razak, Abdul; Karim, La Ode Muhammad; Suhartono, Rizki Mustika; Andara, Darojatun (TAAWUN, 2024)
This Community Service aims to provide knowledge and understanding about preventing and dealing with domestic violence in Sampuabalo mur Village, Buton Regency. It is hoped that this Community Service will be able to provide legal awareness about how to prevent and take action against domestic violence. The methods used in this activity are counseling, lectures, and discussions. The analysis technique used is interviews. The results of the research show that one of the effective efforts to increase public knowledge and awareness is legal counseling carried out in front of the Sampuabalo Village Community the participants present were predominantly married people and were very enthusiastic the community hoped that more legal counseling would be needed so that they could increase their knowledge about the law.